Pengaruh Literasi Keuangan Syariah, Sosialisasi, Dan Jenis Kelamin Terhadap Keputusan Menggunakan Produk Perbankan Syariah Pada Generasi Z Di Jambi - Ferawati, Rofiqoh; Bariatun, Linda (Program Studi Manajemen Keuangan Syariah, 2025)
This study aims to determine the effect of Islamic financial literacy, socialization, and gender on the decision to use Islamic banking products on generation z in Jambi. The method used in this study is a quantitative method, using SPSS 29. The sample in this study was 100 samples of generation z in Jambi, by distributing questionnaires. The results of the study showed that Islamic financial literacy had a significant effect on the decision to use Islamic banking products as evidenced by a sig value of 0.001 < 0.05. Socialization had a significant effect on the decision to use Islamic banking products as evidenced by a sig value of 0.001 <0.05. Gender did not have a significant effect on the decision to use Islamic banking products as evidenced by a sig value of 0.505 > 0.05. Sharia financial literacy, socialization and gender simultaneously have a significant effect on the decision to use sharia banking products, of 0.620 or 62%.